The nicotine-mediated decline in L-dopa-induced dyskinesias is associated with a decrease in striatal dopamine release - Bordia, Tanuja (2013)
L-dopa-induced dyskinesias (LIDs) are a side effect of Parkinson’s disease therapy that is thought to arise, at least in part, because of excessive dopaminergic activity. Thus, drugs that regulate dopaminergic tone may provide an approach to manage LIDs. Our previous studies showed that nicotine treatment reduced LIDs in parkinsonian animal models. The present work investigates whether nicotine may exert its beneficial effects by modulating presynaptic dopaminergic function. Rats were unilaterally lesioned by injection of 6-OHDA (2 × 3 ug per site) into the medial forebrain bundle to yield moderate parkinsonism. They were then implanted with minipumps containing vehicle or nicotine (2.0 mg/kg/d) and rendered dyskinetic with L-dopa (8 mg/kg plus 15 mg/kg benserazide). Lesioning alone decreased the striatal dopamine transporter, nicotinic receptor (nAChR) levels and nAChR-mediated (3)H-dopamine release, consistent with previous results. Nicotine administration reduced L-dopa induced abnormal involuntary movements throughout the course of the study (4 months). Nicotine treatment led to declines in the striatal dopamine transporter, α6β2* nAChRs and various components of α6β2* and α4β2* nAChR-mediated release. L-dopa treatment had no effect. These data suggest that nicotine may improve LIDs in parkinsonian animal models by dampening striatal dopaminergic activity.